RESEPSI PEMUDA MUSLIM DAN NON MUSLIM TERHADAP FILM BULAN TERBELAH DI LANGIT AMERIKA DI KABUPATEN JEMBER - Kartika Bina Kasih (Indonesian Journal of Islamic Communication, 2021)
Films have become an audio-visual communication medium that is familiar to all people of all ages and social backgrounds. The strength and ability of films in reaching many social segments then makes experts that films have the potential to influence audiences. The content of the film itself can consist of various themes, two of which are about race and religion. Like the film Bulan Terbelah Di Langit Amerika. After this film aired, there were pros and cons to the message in the film. Because Bulan Terbelah Di Langit Amerika, America emphasizes more on contemporary Islamic issues that are currently in the spotlight of the world, including Islamophobia. The film, Moon Split in the American Sky, presents Islamophobia as a form of Western ignorance of Islam. This film shows the treatment of American society which denigrates Islam, such as attitudes of religious intolerance, suspicion and hatred towards Muslims and anti-pluralism towards other teachings.Therefore, from several studies on films that discuss racial and religious backgrounds, there must be conflicts based on the different knowledge and experiences that each individual has, so the researcher tries to do reception research that will get the results of the subject. what is examined is that the audience accepts, rejects, or does not fully accept and reject the problem that is given. By using a qualitative approach, researchers chose to conduct research in Jember Regency. As a result, of the four youths studied, namely the Muhammadiyah Youth, IPNU / Nahdlatul Ulama Student Association, the Indonesian Christian Youth Movement and the Catholic Youth Movement, and the four had the same results. Where the four of them are in the dominant hegemonic or receive messages in the film Bulan Terbelah Di Langit Amerika.